Chronic myeloid leukemia — before and after imatinib (Third part) - E. G. Lomaia; M. Yu. Konopleva; E. G. Romanova; A. Yu. Zaritzkiy (Онкогематология)
Imatinib (IM) appearance has changed approaches to chronic myeloid leukemia (CML) therapy. Second generation tyrosine kinase inhibitors (TKI) — nilotinib and dasatinib, developed soon after IM, and are already widely used in CML patients with inefficiency or intolerance of them. Considering availability in clinical practice of tree TKI, allogeneic hematopoietic stem cell transplantation (HSCT) and new preparations development, there is a real treatment of all patients with CML, which was recently considered as fatal disease. In first two parts of article general information about CML, issues concerning HSCT, TKI mechanisms of action and safety are discussed. In this part TKI therapy efficacy and modern treatment recommendation for CML patients in different phases are presented.